Learning Media Modification: Dhako as English Mathematic Learning Media with a Problem-based Learning Approach - Fatoni, Akhmad Feri; Cahyono, Anang Hadi (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2024)
Using traditional game media provides several benefits in teaching and learning activities in the classroom. Previous studies found that giving English numeracy material using Dhako games was effective in increasing vocabulary but less effective in arithmetic operations (addition, subtraction, multiplication, and division). This study aimed to determine the modification of the Dhako game on vocabulary mastery and arithmetic operation skills for 5th-grade students of SDN Aengdake I. The research method used was quantitative: one group pretest and posttest design with data analysis using T-Test analysis. Based on the results of the descriptive analysis, the students' mean pretest = 74.47 and posttest = 89.76. Based on the results of descriptive analysis, the students' mean pretest = 69.56 and posttest = 91.35. Thus, it could be concluded that the provision of Dhako games with a PBL approach significantly affected English numeracy skills. Based on the output table of the ttest results, the value of sig = 0.000 is obtained, which means it was smaller than 0.05. Thus Ho was rejected, and H1 was accepted, meaning that there was an effect of the Dhako game with the PBL approach on improving English numeracy skills for fifth graders at SDN Aengdake 1.